(untitled) (Research, Society and Development, 2022)
Worldwide, there is an increasing incidence of contaminants in aqueous matrices, among them, antibiotics, pesticides and pharmaceutical products. This problem, coupled with the occurrence of these pollutants at trace levels, creates unique challenges for the analytical detection and performance evaluation of the removal of these contaminants from water. The purpose of this experiment was to optimize the operational conditions of the Photo-fentom like process of sodium diclofenac residues by Response Surface Methodology (RSM), based on analysis in aqueous solution. The drug was determined via UV-Vis spectrophotometry using a 23 factorial design with a central point to evaluate the degradation of the sodium diclofenac. The design was composed of two levels and three factors: (X1) Irradiation time, ranging from 2 to 4 h; (X2) Hydrogen peroxide content, ranging from 1 to 7%; and (X3) Fe2+ concentration, ranging from 25 to 100 mg L-1. According to the levels defined for each parameter, the optimized methodology showed that the best degradation of the drug was achieved by combining 2 h of irradiation, 1% Hydrogen peroxide solution and 25 mg L-1 of solution containing Fe2+, where 97.04% of drug degradation was achieved. From ANOVA it could be inferred that the concentration of Fe2+ (p = 0.13044) and the interaction irradiation time with Fe2+ concentration (X1X3) (p = 0.0439) had the highest significance in the degradation process. The experimental planning was useful to indicate the region of maximum degradation, therefore, the methodology was suitable for degradation of residues of this drug in water samples.